Pengembangan Media Pembelajaran Interaktif Berbasis PowerPoint untuk Peningkatan Minat dan Pemahaman Bahasa Inggris Materi Food and Drink di Thailand - Ayyuza, Frizka Kinanti; Rochmawati, Rochmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to develop interactive PowerPoint-based learning media to improve the interest and understanding of Prathom 5 students in Tessaban 2 Ban Sadao, Thailand, specifically on the Foods and Drinks material. The Research and Development (R&D) method with the ADDIE model was used, including analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, pretests and posttests, and validation by three supervising teachers as material, media, and language experts. The results of the paired t-test showed a significant increase with an average posttest score of 80.5 compared to the pretest of 57, while expert validation strengthened the quality of the learning media. Several revisions were made to improve the material, design, and language to better suit student needs. The findings prove that this media is effective in increasing student motivation and learning outcomes. This research can be used as a reference for media development on other materials and various levels of education, as well as improving technological facilities to optimally support interactive learning.